2020
DOI: 10.3389/fmicb.2020.591839
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of an Air Pollutant (NO2) on a Selection of Commensal Skin Bacterial Strains, Potential Contributor to Dysbiosis?

Abstract: The skin constitutes with its microbiota the first line of body defense against exogenous stress including air pollution. Especially in urban or sub-urban areas, it is continuously exposed to many environmental pollutants including gaseous nitrogen dioxide (gNO2). Nowadays, it is well established that air pollution has major effects on the human skin, inducing various diseases often associated with microbial dysbiosis. However, very few is known about the impact of pollutants on skin microbiota. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Compared with SO 2 , NO 2 showed a stronger correlation with the skin indicators 63 . The increase in NO 2 content was accompanied by a decrease in skin oil content and an increase in moisture, which causes reduced acidity of the skin 64,65 . However, the skin tone darkens with the ITA° and becomes more yellow.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with SO 2 , NO 2 showed a stronger correlation with the skin indicators 63 . The increase in NO 2 content was accompanied by a decrease in skin oil content and an increase in moisture, which causes reduced acidity of the skin 64,65 . However, the skin tone darkens with the ITA° and becomes more yellow.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study found that carbon particle treatments upregulated psoriasis-related genes (13) and that pollutants can affect skin diseases by weakening the skin barrier or modifying skin absorption (14,15). Several psoriasis-related skin bacteria are affected by NO 2 (16,17). O 3 can activate cutaneous inflammasomes, which may induce inflammatory skin conditions (18).…”
Section: Resultsmentioning
confidence: 99%
“…Such influence can modulate health effects not only at the respiratory tract level, recent data showed that the exposure to gaseous nitrogen dioxide could contribute to skin dysbiosis, which would affect skin homeostasis; the response of the microbiota to the nitrosative stress could involve pathologies such as atopic dermatitis [32].…”
Section: Introductionmentioning
confidence: 99%